PENERAPAN HAND SANITIZER DENGAN HANDLESS PUMP SYSTEM PADA KEDAI MAKANAN DI BATAM DI ERA NEW NORMAL - Natalis Christian; Ria Karina; Iskandar Itan; Indo Dicaprio P; Raimon R Tampubolon; Rayden Vebrianto; Calvin Pang; M Ramanda Alim; Meirita Sitadewi; Melisa Putri Pane; Indah Novitasari; Vincent Sun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
During the Covid-19 pandemic, one of the main problems that concerned by both the government agencies and the public is the spread of the virus in crowded areas/locations through objects that are often touched by many people. One of the locations that is prone to the spread of the Covid-19 virus is a food restaurant that is crowded with customers. Transactions carried out by customers increase the risk of spreading the virus in the restaurant through door handles, tables, chairs, water taps, or even money. This research was conducted to reduce the risk of spreading the covid-19 virus by implementing a handless pump system on hand sanitizers. One location that applies the results of this research is Kedai Ramly which is located in Bengkong District, Batam Island. Driven by the owner's great sense of responsibility and empathy, the use of a handless pump system has been successfully implemented. The implementation shows satisfactory results as evidenced by the increasing customer trust in the hygiene standards applied at Kedai Ramly.